Response of peanut quality and yield to chicken manure combined with Rhizobium inoculation in sandy soil - Chuong, Nguyen Van (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
Chemical fertilizers, which contain a nitrogen (N) element, has been intensively used to increase the peanut productivity. However, the unstable and high cost of N fertilizer, and the great demand for N fertilizer sources have strongly increased the strategical plan of nitrogen fixation (NF). Therefore, the field research was carried out to appraise the ability of Rhizobium sp. trains and chicken manure (CM) on the quality and yield of peanuts. This research has four ratios, which valued from 0.0, 2.0, 4.0 to 6.0 t CM per ha in the combination with the Rhizobium sp. inoculum, expect control treatment (without CM and Rhizobium sp.). Different rates of CM combined with Rhizobium sp. inoculation was added by using 6.0 tons CM/ ha, which had number of the highest peanut nodules. Research results observed that the inoculant of Rhizobium sp. strain combined with CM remarkably increased the yield components per plant such as biomass, number of nodules, weight of dry nodules, weight of fill and empty pods and fresh yield of groundnut. The highest yield and quality of peanut (7.60 t/ha), oil % (50.6%), seed protein percentage (26.8%), as well as NPK content in seed (4.32, 0.912 and 0.999%, respectively) were obtained under the application of NPK+6.0 t CM/ha+ Rhizobium sp. inoculation. Co-application of 6t CM/ha and Rhizobium sp. inoculation increased by 20.5% when compared without CM application and no Rhizobium sp. inoculation. The study showed that both possibility of nitrogen fixation of peanut and nitrogen uptake of the sandy soil were raised by field inoculant with effectiveness of Rhizobium sp. with animal manure application. In really, Rhizobium sp. inoculation and CM proved a great method to increase soil nutrients for subsequent crops and it helped to enhance the taking of nitrogen from the air into the crop soil.